2014
DOI: 10.1038/mt.2014.179
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of ACE2/Ang-(1–7) Bioencapsulated in Plant Cells Protects against Experimental Uveitis and Autoimmune Uveoretinitis

Abstract: Hyperactivity of the renin-angiotensin system (RAS) resulting in elevated Angiotensin II (Ang II) contributes to all stages of inflammatory responses including ocular inflammation. The discovery of angiotensin-converting enzyme 2 (ACE2) has established a protective axis of RAS involving ACE2/Ang-(1-7)/Mas that counteracts the proinflammatory and hypertrophic effects of the deleterious ACE/AngII/AT1R axis. Here we investigated the hypothesis that enhancing the systemic and local activity of the protective axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 50 publications
0
90
0
Order By: Relevance
“…CNTB fusion proteins expressed in chloroplasts form pentameric structures that are highly resistant to detergents, and this hampers solubilization due to tight interactions between CNTB monomers, mediated by 30 hydrogen bonds, seven salt bridges, and hydrophobic interactions (Miyata et al, 2012). In our previous studies (Boyhan and Daniell, 2011;Kwon et al, 2013;Kohli et al, 2014;Shil et al, 2014), multimeric forms exist even after treatment with DTT, detergents (SDS), and boiling. Also, acid (pH 2) could not completely dissociate CNTB pentamers due to the reformation of multimeric structures.…”
Section: New Solution For the Quantitation Of Insoluble Multimeric Prmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTB fusion proteins expressed in chloroplasts form pentameric structures that are highly resistant to detergents, and this hampers solubilization due to tight interactions between CNTB monomers, mediated by 30 hydrogen bonds, seven salt bridges, and hydrophobic interactions (Miyata et al, 2012). In our previous studies (Boyhan and Daniell, 2011;Kwon et al, 2013;Kohli et al, 2014;Shil et al, 2014), multimeric forms exist even after treatment with DTT, detergents (SDS), and boiling. Also, acid (pH 2) could not completely dissociate CNTB pentamers due to the reformation of multimeric structures.…”
Section: New Solution For the Quantitation Of Insoluble Multimeric Prmentioning
confidence: 99%
“…Therefore, transgenes inserted into chloroplast genomes are expressed at high levels, up to 70% of total leaf protein (De Cosa et al, 2001;Ruhlman et al, 2010). A wide range of proteins, from very small antimicrobial peptides (Lee et al, 2011) or hormones (Boyhan and Daniell, 2011;Kwon et al, 2013) to very large proteins encoded by bacterial, viral, fungal, animal, and human genes, have been expressed successfully in plant chloroplasts (DeGray et al, 2001;Daniell et al, 2009;Verma et al, 2010;Shenoy et al, 2014;Sherman et al, 2014;Shil et al, 2014). Most importantly, expressed proteins are highly stable when lyophilized plant cells are stored at ambient temperature (Kwon et al, 2013;Lakshmi et al, 2013;Kohli et al, 2014;Jin and Daniell, 2015).…”
mentioning
confidence: 99%
“…21,36 On the other hand, ACE2 deletion exaggerated Ang II-induced expressions of inflammatory cytokines. 57 Here, we found that overexpression of ACE2 inhibited Ab-induced inflammatory responses in human RPE cells.…”
Section: Ace2 Reduces Ab-induced Inflammation In Human Rpementioning
confidence: 99%
“…[27][28][29][30] Most components of RAS, including ACE2/Ang-(1-7)/Mas axis, have been confirmed in various tissues and organs, including the eye. 21,31,32 Our previous study showed that activation of ACE2 alleviated the lipopolysaccharide (LPS)-induced inflammatory response in both human RPE cells 33 and in endotoxin-induced uveitis (EIU) mouse/rat models. 34,35 Moreover, the most recent study from our laboratory demonstrated that adeno-associated virus (AAV)-mediated ACE2 gene delivery alleviated the ocular inflammation in experimental autoimmune uveitis (EAU) mouse model by activating the local ACE2/Ang-(1-7)/Mas axis.…”
Section: 20mentioning
confidence: 99%
See 1 more Smart Citation